2017
DOI: 10.1007/s40263-017-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Smoking Cessation in Individuals with Schizophrenia: Special Considerations

Abstract: Premature mortality due to cardiovascular disease in those with schizophrenia is the largest lifespan disparity in the US and is growing; adults in the US with schizophrenia die on average 28 years earlier than those in the general population. Smoking prevalence among individuals with schizophrenia is estimated to be from 64–79%. Smokers with schizophrenia have historically been excluded from most large nicotine-dependence treatment studies. Converging evidence, however, indicates that a majority of smokers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 89 publications
2
64
0
1
Order By: Relevance
“…Because smoking is common in patients with serious mental illness, it has also been an important target of behavioral interventions, with mixed results (Cather et al, 2017;McGinty et al, 2016). Smoking rates in patients with serious mental illness have declined much less than in those without such disorders (Cook et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Because smoking is common in patients with serious mental illness, it has also been an important target of behavioral interventions, with mixed results (Cather et al, 2017;McGinty et al, 2016). Smoking rates in patients with serious mental illness have declined much less than in those without such disorders (Cook et al, 2014).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The results of our study indicate that smoking is highly prevalent among schizophrenia patients, and even more prevalent among patients with HS and schizophrenia. The association between smoking and HS, as well as that between smoking and schizophrenia, is both well‐established . Moreover, it has been suggested that patients suffering from mental illnesses often smoke in an effort to relieve symptoms and associated distress, or to restore dopamine following a blockade caused by certain medications and diminish its side effects .…”
Section: Discussionmentioning
confidence: 99%
“…Addressing cigarette smoking more vigorously would provide one strategy to reduce the excess mortality in this population. It is now established that many persons with serious mental illness can and do want to quit smoking , that there are smoking cessation treatments that are safe and effective , and that quitting also confers mental health benefits .…”
Section: Discussionmentioning
confidence: 99%